Variability in Sclerotium oryzae isolates causing stem rot of rice based on cultural, morphological and pathogenic behaviour from Haryana regions - KUMAR, A.; SINGH, RAM; JALALI, B.L. (Indian Phytopathology, 2011)
Fifteen isolates of rice stem rot fungus Sclerotium oryzae Catt. (SO1 – SO15) were examined for their variability. These isolates were collected from major cultivars and locations of Haryana state. The isolates exhibited variation in their growth, sclerotial position and pattern on potato dextrose agar. Out of ten, six rice genotypes viz. BR 51-282-8-HR 45, BRC 16-127-4-1, CR 689-116, CR 837, HKR 126 and PR 106 showed differential response against the pathogen. On the basis of pathogenic behaviour, the isolates were categorised into four pathogenic groups. Accordingly, these six rice genotypes could be used as differential hosts for study of host-pathogen interaction for an efficient rice resistant breeding programme against stem rot.